Plan estratégico para la empresa “D' Maderas y algo más” periodo 2023-2028 - Intriago Peñarrieta, Héctor Adonis (2023)
The general objective of this research was to design a strategic plan that contributes to the improvement of the administrative management for the D'maderas y algo más microenterprise and something else during the period 2023-2028, in order to fulfill this objective it was necessary to carry out a situational study of the factors internal, through the interview with the manager Mr. Héctor Aníbal, it was learned that the business had not established a strategic plan that would allow it to set objectives that can be achieved in the short, medium and long term, in addition to not having the FODA tool for the development of strategies based on the main strengths, weaknesses, opportunities and threats; then an external analysis of the current situation of the hardware store was carried out through a customer survey, with which the external reality faced by the business was understood, followed by the PEST analysis, analysis of the 5 forces Porter, and the matrix of external factors that resulted in a weighted total of 2.74, indicating that the strategies and opportunities that the microenterprise has in the market are being used efficiently; In addition, a strategic plan was carried out that included the main commercial, technical and financial aspects that allow the business to have optimal administrative management, and finally, with the help of the 5w + 1h matrix, the actions to be developed were planned to comply with the growth, defense, adaptation and survival strategies proposed.